The impact of Debt Structure on Firm Investments: Empirical Evidence from Turkey - Aygun, Mehmet; IC, Suleyman; Sayim, Mustafa (Archives of Business Research, 2014)
The purpose of this study is to examine the impact of corporate debt structure on firm investments in Turkey. The regression and correlation analysis reveal a significant positive effect between corporate debt structure and firm investments. This effect is relatively strong for companies with high growth opportunities compare to companies with low growth opportunities. Consistent with the existent literature these findings provide support that a higher level of long-term debt in total debt structure reduces investments for firms with high growth opportunities. These effects need, therefore, to be incorporated in debt structure for Turkish firms to support their assets with proper financing sources.